Socio-Spatial Segregation as a Consequence of Commercial Gentrification in the Centrality of Cumbayá, Quito-Ecuador - Unda-Padilla, Javier (2023)
The process of urban expansion of Quito has caused the formation of new peripheral centralities, the same ones that offer all the services that the traditional center grants, thanks to public and private investment. In this sense, citizens from wealthy social strata are attracted to reside in these new sectors where consumption, exclusivity and privatization of space become the new way of life that conditions the social dynamics of the territory. This article seeks to identify the types of urban segregation that have occurred from the phenomenon of commercial gentrification evidenced on the edges of the Central Park of Cumbayá between the years 2000 and 2022. For this, a mixed research methodology is used where interviews, photographic archives and surveys allow generating a socio-spatial analysis that evidences this phenomenon. As a result, it was found that commercial gentrification not only has displaced old residents of the sector but also created stigmatization and segregation. Finally, is evidenced that few traditional citizens have resistance to abandon their place of origin and have raised their voices against this urban phenomenon.